Analysis of Content Benefits of Audiovisual Learning Models For Nonformal Early Children and Basic Education - Zulkarnain, Rufran; Herman, Herman (Devotion : Journal of Research and Community Service, 2022)
This research is to describe the duties and responsibilities of the Bengkulu Province PAUD and Dikmas Development Center (BP PAUD) which must be carried out by tutors and teachers, namely, the development of learning models. The Bengkulu Province PAUD and Dikmas Development Center (BP PAUD) has created a development product entitled social-financial learning through Audio Visual for Non-Formal PAUD Children and Basic Education to support children's learning from home. This research method uses descriptive qualitative research methods, data collection techniques use interview techniques, observation and documentation, data validation techniques use time triangulation techniques, subject triangulation and technical triangulation, the subjects in this study are Non-Formal PAUD managers and Basic Education managers who implement development the Daily Learning Implementation Plan (RPPH) model in Non-Formal PAUD and Basic Education. To ensure the benefits of the model development product by the manager, this research was carried out. The purpose of this study was to find out the benefits of teaching materials about financial social learning strategies in the Daily Learning Implementation Plan (RPPH), namely to help educators and students focus on learning in accordance with the teaching materials that have been provided, and the benefits of financial learning activities through Audio Visual for PAUD Children Non-formal and Basic Education in the Daily Learning Implementation Plan (RPPH), namely to support learning from and make the implementation of learning more focused, directed because it takes advantage of children's hearing and sight so that children become interested and active in learning while the benefits of RPPH content are about Audio Visual learning for identity because in the RPPH there are already themes and sub-themes, another benefit of the Daily Learning Implementation Plan (RPPH) is to make the implementation of learning more focused and directed, especially for Non-formal PAUD Children and Basic Education